2016
DOI: 10.1111/jog.13180
|View full text |Cite
|
Sign up to set email alerts
|

Association between nephrinuria, podocyturia, and proteinuria in women with pre‐eclampsia

Abstract: Aim Podocyte depletion in the kidney is associated with end‐stage kidney disease (ESKD). Pre‐eclampsia (PE) increases the risk of ESKD in later life. This study was performed to determine whether nephrinuria (soluble nephrin in the urine) is correlated with proteinuria and/or podocyturia (podocytes in the urine) in PE women. Methods Eighty‐three urine samples, consisting of 45 and 38 samples from 27 normotensive and nine PE women, respectively, underwent simultaneous determination of nephrin, protein, and crea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
10
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 33 publications
(95 reference statements)
1
10
0
Order By: Relevance
“…As FPR was consistently predictive of later PE in most studies6789101112131415161718192021222324, FPR has been accepted as a diagnostic aid for PE in conjunction with other clinical findings26. This was also confirmed in the present study; women with FPR >90 th percentile value had RR of PE = 4.98 (1.91–13.0) compared to women with FPR <90 th percentile value.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…As FPR was consistently predictive of later PE in most studies6789101112131415161718192021222324, FPR has been accepted as a diagnostic aid for PE in conjunction with other clinical findings26. This was also confirmed in the present study; women with FPR >90 th percentile value had RR of PE = 4.98 (1.91–13.0) compared to women with FPR <90 th percentile value.…”
Section: Discussionsupporting
confidence: 85%
“…The podocytes are glomerular epithelial cells located at the outermost layer of the glomerular basement membrane (GBM)7 and form the final barrier to protein loss8. Glomerular podocytes with reduced nephrin expression are likely to detach from the GBM, and podocyturia as a result from podocytes detachment from the GBM is associated with increased nephrinuria and proteinuria in women with PE910. These suggested that glomerular podocytes that had shed nephrin were impending detachment from the GBM and the shed nephrin became nephrinuria.…”
mentioning
confidence: 99%
“…Podocyturia can be monitored via mRNA expression of podocyte‐specific proteins, such as podocin and nephrin, and increases with increasing proteinuria in pregnancy complicated with PE . Certain stimuli, however, cause alteration of the phenotype of glomerular podocytes, that is, reduced nephrin mRNA expression in the glomerular podocytes (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…[2][3][4][5][6][7] Given that podocytes are terminally differentiated cells 1 and their turnover rate is very low, 8,9 the detachment of glomerular podocytes from the GBM contributes to a decrease in the number of glomerular podocytes in the kidneys. 1,10 Podocyturia can be monitored via mRNA expression of podocyte-specific proteins, such as podocin and nephrin, 7,11,12 and increases with increasing proteinuria in pregnancy complicated with PE. 7,11,12 Certain stimuli, however, cause alteration of the phenotype of glomerular podocytes, that is, reduced nephrin mRNA expression in the glomerular podocytes (i.e.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation